EFFECT OF VITAMIN D ON FERTILITY IN POLYCYSTIC OVARIAN SYNDROME (The Research of Medical Science Review, 2025)
OBJECTIVE: To determine the association of vitamin D status and fertility outcomes in women with polycystic ovarian syndrome.METHODOLOGY: In this cross-sectional study conducted at the Jinnah Postgraduate Medical Centre, Karachi a total of 275 female patients with polycystic ovary syndrome (PCOS) were included to study the effect of vitamin D on reproductive function. Participants were carefully recruited according to the Rotterdam criteria with a rationale of excluding subjects presenting with other endocrine disorders or had treatment of fertility in the past. Detailed analyses were performed on serum concentrations of vitamin D and ovulatory function, as well as metabolic indices. The data was analyzed using version 26 of SPSS, and p ≤ 0.05 was considered statistically significant.RESULTS: The investigation encompassed a cohort of 275 females diagnosed with Polycystic Ovary Syndrome (mean age 26.19 ± 5.21 years). Infertile participants exhibited markedly diminished levels of vitamin D (11.95 ± 5.86 ng/mL) in comparison to their fertile counterparts (16.71 ± 5.25 ng/mL, p=0.0001). The incidence of vitamin D deficiency was significantly higher among infertile women (85.3% vs. 74.4%, p=0.033). Elevated testosterone concentrations, insulin resistance (HOMA-IR: 3.42 vs. 3.01, p=0.008), as well as waist-to-hip ratio, were also correlated with infertility.CONCLUSION: The findings reveal a strong correlation of vitamin D deficiency with reproductive problems in women with polycystic ovary syndrome (PCOS). Women with infertility had vitamin D levels that were significantly lower than others and those levels were associated with insulin sensitivity, hormonal disorders and ovulatory problems. However, more research is needed to determine the best treatment methods. Furthermore, supplementation of vitamin D should be incorporated within the management of PCOS, especially in those women with challenges in achieving pregnancy, and the vitamin D levels need to be monitored on regular basis.